Implementasi Peraturan Gubernur Jawa Timur Nomor 30 Tahun 2018 Tentang Penyelenggaraan Pendidikan Inklusif Provinsi Jawa Timur - Gangsar Mujiharto; Suwarno Suwarno; Teguh Pramono (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Education is a human need that must be fulfilled. Permendiknas No. 70 of 2009 concerning Inclusive Education for Learners with Disabilities and Potential for Special Intelligence and/or Talent. This research examines the "Implementation of East Java Governor Regulation Number 30 of 2018 concerning the Implementation of Inclusive Education in East Java Province (Study at Putera Asih Special School (SLB) Putera Asih Kota Kediri)". This research approach is descriptive qualitative. The data in this study consisted of primary data and secondary data related to the focus of the research. Data collection techniques used are interviews, observation, and documentation. While the research instrument is the researcher himself, and some supporting tools. Data analysis techniques are carried out through the process of data collection, data presentation, and conclusion drawing. This research was conducted to describe the implementation of inclusive education policies at Putera Asih Special School (SLB) in Kediri. The results of this study indicate that the implementation of the Inclusive Education Policy at the Putera Asih Special School (SLB) in Kediri City is not yet optimal because there are still many obstacles. then the school must actively cooperate with both the government and other parties that support the achievement of the desired goals